(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Canadian literature, in general, consists of two mainstreams, French and English writings. French writings in Canada often describe Quebec and English writings in Canada often describe Ontario. The Nobel Laureate Alice Munro paints the rural Ontario in most of her works. They are very regional and often becoming the colourful threads of a national dream. She was once called as a regional writer for her regional descriptions. Reading her in deep, a reader can understand the supreme universal themes. She gives clear picture of landscape, environment and climatic condition in her works. She focuses more on places than on human characters. Her works frequently centres on the culture of rural Ontario, Canada. The descriptions of those regional elements spring from the joys and sorrows of the local people and their longings to bring about healthy changes. The layers of Munro’s works are simultaneously the old and the new and the regional and the national. Hence, Alice Munro’s short story Collection Dear Life can be called as “Literature of Ontario.”